Carbon nanotube dispersion liquid, carbon nanotube resin composition, composition for electrode, electrode film, and secondary battery
Patent Information
- Application Number
- JP2023142457
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-09-01
- Publication Date
- 2025-03-13
AI Technical Summary
【0014】 本発明の一実施形態によれば、初期の流動性に優れ、かつ経時後も高い流動性を維持し、ライフサイクルが長く、かつ操作性にも優れたカーボンナノチューブ分散液を提供できる。 また、良好なサイクル特性を有する二次電池を形成可能なカーボンナノチューブ分散液、カーボンナノチューブ樹脂組成物、電極用組成物、および電極膜を提供することができる。
Smart Images

Figure 2025035426000001_ABST
Abstract
Description
[Technical field]
[0001] An embodiment of the present invention relates to a carbon nanotube dispersion, a carbon nanotube resin composition, an electrode composition, an electrode film, and a secondary battery. [Background technology]
[0002] With the spread of electric vehicles and the miniaturization and weight reduction of portable devices with high performance, there is a demand for secondary batteries with high energy density and higher capacity. In this context, lithium-ion secondary batteries in particular are being used in many devices.
[0003] One method for increasing the capacity of lithium-ion secondary batteries is to increase the amount of silicon-based active material added to the negative electrode. Examples of negative electrode active materials include graphite and silicon-based active materials, and silicon-based active materials in particular are expected to increase the capacity of batteries because of their large theoretical capacity. However, silicon-based active materials undergo significant volumetric changes during charging and discharging, so there is a demand for electrode materials that can follow the volumetric changes of silicon-based active materials.
[0004] In lithium ion secondary batteries, carbon black, ketjen black, graphene, carbon fiber, etc. are used as conductive materials. In particular, carbon nanotubes, a type of carbon fiber, can efficiently form a conductive network with a small amount, so that it is possible to reduce the electrode resistance and improve the load resistance of the battery. In addition, it can improve the strength of the electrode and follow the expansion and contraction of the silicon-based active material, so that the cycle life of the lithium ion secondary battery can be improved.
[0005] In recent years, carbon nanotubes are generally added to electrode compositions by using a carbon nanotube dispersion. In order to maintain uniformity in the electrode composition, the operability when using the carbon nanotube dispersion is very important, and the carbon nanotube dispersion must have excellent fluidity in order to add easily and uniformly. The long-term storage stability of the dispersion is important, and if the stability over time is excellent, there is no restriction on the storage or transportation period, and the product value is high. Therefore, the stability over time of the dispersion is also important, and it is necessary for the carbon nanotube dispersion after the aging to have excellent fluidity. In the case of a carbon nanotube dispersion that has no fluidity or is extremely unstable, there is a risk that it cannot be taken out of the container or that it is difficult to transport through piping. However, carbon nanotubes are usually formed by entanglement of carbon fibers having a nano-sized outer diameter to form aggregates, and it is very difficult to defibrate and disperse them, and even if the initial fluidity is good, it is difficult to maintain the dispersion stability and fluidity of the carbon nanotube dispersion during transportation or use after storage.
[0006] Furthermore, if the fluidity is poor, the carbon nanotubes will not be distributed uniformly in the electrode composition when mixed with the active material, and when made into an electrode, localization of the carbon nanotubes will occur, making it impossible to form a conductive network, and it will not be possible to reduce the electrode resistance or improve the load resistance of the battery, resulting in problems with the electrical characteristics. In recent years, the use of water as a dispersion medium has attracted attention from the perspective of reducing environmental impact and cutting costs. However, due to the high hydrophobicity of carbon nanotubes, it tends to be more difficult to maintain fluidity and stability over time when dispersed in water.
[0007] In Patent Document 1, the use of a polymer dispersant and a binder resin containing a structural unit derived from (meth)acrylic acid makes it possible to disperse carbon nanotubes in water. Furthermore, Patent Document 2 discloses a technique for dispersing carbon nanotubes at a high concentration in water by controlling the weight average molecular weight and degree of etherification of carboxymethyl cellulose and using such carboxymethyl cellulose as a dispersant. [Prior art documents] [Patent documents]
[0008] [Patent Document 1] JP 2019-212496 A [Patent Document 2] Patent Publication No. 2021-176140 Summary of the Invention [Problem to be solved by the invention]
[0009] However, Patent Document 1 does not achieve dispersion of carbon nanotubes at a high concentration of several mass percent or more. If the concentration of carbon nanotubes is low, problems arise such as reduced design freedom when mixing materials such as active materials and binders, and high transportation costs per unit of carbon nanotube solid content, so there is a demand for a high-concentration carbon nanotube dispersion that has excellent initial fluidity and stability over time. Furthermore, in Patent Document 2, the stability over time of the carbon nanotube dispersion in which carbon nanotubes are dispersed at a high concentration is not fully considered, and there is room for improvement in terms of operability with respect to the viscosity fluidity of the dispersion over time.
[0010] In other words, the object of the present invention has been made in consideration of the above-mentioned circumstances, and aims to provide a carbon nanotube dispersion liquid that has excellent initial fluidity, maintains high fluidity even over time, has a long life cycle, and is easy to operate. Another object of the present invention is to provide a carbon nanotube dispersion, a carbon nanotube resin composition, an electrode composition, and an electrode film that are capable of forming a secondary battery having good cycle characteristics.
[0011] Furthermore, an object of the present invention is to provide a carbon nanotube dispersion that has excellent fluidity over time even in the case of a carbon nanotube dispersion containing carbon nanotubes at a high concentration. [Means for solving the problem]
[0012] In order to solve the above problems, the inventors conducted extensive research and discovered that by using two types of dispersants, dispersant (A) and dispersant (C), for carbon nanotubes having a specific specific surface area and controlling the amounts added, a carbon nanotube dispersion that solves the above problems can be obtained, and thus completed the present invention.
[0013] That is, the present invention is as follows. <1> A dispersion medium comprising carbon nanotubes, a dispersant (A), a dispersant (C), and water, The dispersant (A) is a polymer containing 80 mass% or more of structural units derived from (meth)acrylic acid, The dispersant (C) is carboxymethyl cellulose or a salt thereof, A carbon nanotube dispersion liquid that satisfies all of the following (Formula 1) to (Formula 4). (Formula 1) 100≦X≦1200 (Equation 2) Y>0.01 (Formula 3)-0.0005X+0.29≦Y≦-0.0032X+4.32 (Formula 4)0.05X≦Z≦0.16X ((Formula 1) to (Formula 4), X is the specific surface area of the carbon nanotube [m 2 / g], Y is the ratio of the content of dispersant (C) to the content of dispersant (A) [(C) / (A)], Z is the total content of dispersant (A) and dispersant (C) relative to 100 parts by mass of carbon nanotubes. <2> The dispersant (A) is poly(meth)acrylic acid. <1> The carbon nanotube dispersion liquid according to claim 1. <3> The total content of carbon nanotubes, dispersant (A), and dispersant (C) is 90 mass% or more based on the amount of non-volatile components in the carbon nanotube dispersion. <1> or <2> The carbon nanotube dispersion liquid according to claim 1. <4> The viscosity of the carbon nanotube dispersion after 7 days at 40°C, measured using a Brookfield viscometer at 25°C and 6 rpm, is 20,000 mPa s or less. <1> ~ <3> The carbon nanotube dispersion liquid according to any one of the above. <5> pH is between 3.0 and 7.0. <1> ~ <4> The carbon nanotube dispersion liquid according to any one of the above. <6> <1> ~ <5> A carbon nanotube resin composition comprising any one of the carbon nanotube dispersions and a binder resin. <7> <6> A composition for an electrode comprising the carbon nanotube resin composition and an electrode active material. <8> <7> An electrode film formed from the electrode composition described above. <9> A secondary battery including a positive electrode and a negative electrode, At least one of the positive electrode and the negative electrode is <8> A secondary battery having the electrode film described above. Effect of the Invention
[0014] According to one embodiment of the present invention, it is possible to provide a carbon nanotube dispersion liquid which has excellent initial fluidity, maintains high fluidity even after aging, has a long life cycle, and is easy to operate. It is also possible to provide a carbon nanotube dispersion, a carbon nanotube resin composition, an electrode composition, and an electrode film that are capable of forming a secondary battery having good cycle characteristics.
[0015] Furthermore, even in the case of a carbon nanotube dispersion containing carbon nanotubes at a high concentration, it is possible to provide a carbon nanotube dispersion that has excellent fluidity even after aging. [Brief description of the drawings]
[0016] [Figure 1]FIG. 1 is a graph showing an example of the relationship between the specific surface area (X) of the carbon nanotubes used in the examples and comparative examples of the present invention and the ratio (Y) of the content of dispersant (C) to the content of dispersant (A) in the carbon nanotube dispersions prepared in the examples and comparative examples. [Diagram 2] FIG. 2 is a graph showing an example of the relationship between the specific surface area (X) of the carbon nanotubes used in the examples and comparative examples of the present invention and the total content (in parts by mass) of dispersant (A) and dispersant (C) per 100 parts by mass of carbon nanotubes in the carbon nanotube dispersions prepared in the examples and comparative examples. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0017] Hereinafter, the carbon nanotube dispersion, the carbon nanotube resin composition, the electrode composition, and the secondary battery according to the embodiments of the present invention will be described in detail. The present invention is not limited to the following embodiments, and includes embodiments that are implemented within the scope of the present invention. In this specification, a numerical range indicated using "~" indicates a range including the numerical values before and after "~" as the minimum and maximum values, respectively. In the numerical ranges described in stages in this specification, the upper limit or lower limit of a numerical range of a certain stage can be arbitrarily combined with the upper limit or lower limit of a numerical range of another stage. Moreover, the term "main component" refers to the component that is blended in the largest amount among the components. Hereinafter, in this specification, carbon nanotubes will be referred to as "CNT", carboxymethyl cellulose as "CMC", polyacrylic acid as "PAA", polymethacrylic acid as "PMA", carbon nanotube dispersion as "dispersion" or "CNT dispersion", and carbon nanotube resin composition as "resin composition" or "CNT resin composition". In addition, in this specification, unless otherwise specified, the terms "(meth)acrylic", "(meth)acryloyl", "(meth)acrylic acid", "(meth)acrylate", and "(meth)acryloyloxy" respectively mean "acrylic or methacrylic", "acryloyl or methacryloyl", "acrylic acid or methacrylic acid", "acrylate or methacrylate", and "acryloyloxy or methacryloyloxy".
[0018] In addition, the CNT dispersion in the embodiment of the present invention means a state before the binder resin and the electrode active material are added, and the CNT resin composition means a state before the electrode active material is added. In this respect, the CNT dispersion and the CNT resin composition are distinguished from an electrode composition containing an electrode active material. That is, the CNT dispersion does not substantially contain a binder resin and an electrode active material, and the CNT resin composition does not substantially contain an electrode active material. This concept excludes situations in which binder resin and active material are intentionally added to the CNT dispersion, and the total content of carbon nanotubes, dispersant (A), and dispersant (C) should be 90 mass% or more, based on the amount of non-volatile components in the CNT dispersion (100 mass%). This concept excludes the state in which a binder resin is intentionally added to a CNT dispersion, and the binder resin may be 1% by mass or less, 0.5% by mass or less, or 0.1% by mass or less based on the amount of non-volatile components of the CNT dispersion (100% by mass). The binder resin will be described later. This concept excludes the state in which an electrode active material is intentionally added to a CNT dispersion liquid or a CNT resin composition, and the electrode active material may be 1 mass % or less, 0.5 mass % or less, or 0.1 mass % or less, or may be 0 mass %, based on the total mass of the non-volatile components of the CNT dispersion liquid or the CNT resin composition (100 mass %). The electrode active material is described below.
[0019] Unless otherwise noted, the various components appearing in this specification may be used independently as a single type or as a mixture of two or more types. The numerical values specified in this specification are values determined by the methods disclosed in the embodiments or examples. In this specification, "Mw" is the weight average molecular weight in terms of polystyrene determined by gel permeation chromatography (GPC) measurement.
[0020] ≪CNT dispersion liquid≫ The CNT dispersion of the present embodiment contains carbon nanotubes, a dispersant (A), a dispersant (C), and water, The dispersant (A) is a polymer containing 80 mass% or more of structural units derived from (meth)acrylic acid, The dispersant (C) is carboxymethyl cellulose or a salt thereof, All of the following (Equation 1) to (Equation 4) are satisfied. (Formula 1) 100≦X≦1200 (Equation 2) Y>0.01 (Formula 3)-0.0005X+0.29≦Y≦-0.0032X+4.32 (Formula 4)0.05X≦Z≦0.16X ((Formula 1) to (Formula 4), X is the specific surface area of the carbon nanotube [m 2 / g], Y is the ratio of the content of dispersant (C) to the content of dispersant (A) [(C) / (A)], Z is the total content (parts by mass) of dispersant (A) and dispersant (C) relative to 100 parts by mass of carbon nanotubes.
[0021] By using dispersant (A) and dispersant (C) as dispersants for CNTs having such a specific specific surface area and controlling the amounts added, it is possible to obtain a CNT dispersion that has excellent initial fluidity and maintains its fluidity over time, has a long life cycle, and is easy to use. By using the CNT dispersion of the present invention, even if the CNTs are at a high concentration, the fluidity can be maintained over time.
[0022] This effect can be attributed to the following reasons. Both dispersant (A) and dispersant (C) have carboxyl groups, which act as adsorption points and disperse CNTs. Dispersant (A) has more carboxyl groups per unit monomer, so it is presumed that dispersant (A) has higher dispersibility. Generally, the larger the specific surface area of CNTs, the worse the dispersibility of CNTs becomes, making them more difficult to disperse. Therefore, when the specific surface area of CNTs is large, the ratio of dispersant (A) must be increased to increase dispersibility. When the specific surface area of CNTs is small, if the amount of dispersant (A) is large, the excess carboxyl groups do not disperse CNTs, but rather strengthen the interaction between dispersants and promote gelation, so the ratio of dispersant (A) must be decreased. Therefore, by appropriately selecting the total content of dispersant (A) and dispersant (C) and their ratio in accordance with the specific surface area of the CNTs, not only can the dispersant be sufficiently adsorbed to the CNTs and the initial fluidity can be increased, but also detachment of the dispersant from the CNT dispersion can be suppressed even after the passage of time due to transportation or storage, making it possible to maintain stability over time.
[0023] X is the specific surface area of the carbon nanotube [m 2 / g], satisfying formula 1. (Formula 1) 100≦X≦1200
[0024] Y is the ratio of the content of the dispersant (C) to the content of the dispersant (A) [(C) / (A)], and satisfies (Equation 2) and (Equation 3). (Equation 2) Y>0.01 (Formula 3)-0.0005X+0.29≦Y≦-0.0032X+4.32
[0025] Y>0.01, more preferably Y>0.05, and further preferably Y>0.1. When Y is in the above range, the dispersant (C) serves as an acidic buffer solution, and the stability over time can be further improved.
[0026] The relationship is -0.0005X+0.29≦Y, preferably -0.0005X+0.5≦Y, more preferably -0.0008X+0.8≦Y, and further preferably -0.001X+1.0≦Y. Y≦-0.0032X+4.32, preferably Y≦-0.0027X+3.5, more preferably Y≦-0.0017X+2.2, and even more preferably Y≦-0.0012X+1.5. When Y is within the above range, the number of carboxyl groups in dispersant (A) and dispersant (C) relative to the CNTs in the dispersion becomes appropriate, and gelation over time is further suppressed.
[0027] Z is the total content (parts by mass) of dispersant (A) and dispersant (C) relative to 100 parts by mass of carbon nanotubes, and satisfies (Equation 4). (Formula 4)0.05X≦Z≦0.16X
[0028] 0.05≦Z, preferably 0.055≦Z, and more preferably 0.07≦Z. Also, Z≦0.16X, more preferably Z≦0.13X, and more preferably Z≦0.11X. When Z is within the above range, sufficient dispersibility can be obtained for CNTs having a specific specific surface area, dispersibility is improved, and interactions between excess dispersants are eliminated, thereby suppressing gelation.
[0029] The pH of the CNT dispersion is preferably 3.0 or more, more preferably 4.0 or more, and is preferably 7.0 or less, more preferably 6.0 or less. A pH of 3.0 or higher is preferable because the hydrogen bonds between the carboxyl groups of dispersant (A) and dispersant (C) are adequate, and gelation can be suppressed. A pH of 7.0 or lower is preferable because the adsorption ability of the carboxyl groups is adequate, and the viscosity of the CNT dispersion after static storage can be kept low.
[0030] The lower the viscosity of the CNT dispersion after 7 days at 40°C, measured using a Brookfield viscometer at 25°C and a rotation speed of 6 rpm, the better, and it is preferably 20,000 mPa·s or less, more preferably 17,500 mPa·s or less, even more preferably 15,000 mPa·s or less, and particularly preferably 10,000 or less. If the viscosity of the CNT dispersion after 7 days at 40°C, measured using a Brookfield viscometer at 25°C and a rotation speed of 6 rpm, is within the above range, it can be said that the dispersion has sufficient fluidity and excellent operability.
[0031] <Carbon nanotubes (CNTs)> CNTs have a shape in which planar graphite is wound into a cylindrical shape. Single-walled CNTs have a structure in which one layer of graphite is wound into a cylindrical shape. Multi-walled CNTs have a structure in which two or more layers of graphite are wound into a cylindrical shape. In addition, the sidewalls of CNTs do not have to have a graphite structure. For example, CNTs with sidewalls having an amorphous structure can also be used as CNTs.
[0032] The CNTs of this embodiment may be either single-walled CNTs or multi-walled CNTs, or may be a mixture of single-walled CNTs and multi-walled CNTs. The number of walls of the CNTs is preferably 30 or less, more preferably 20 or less, and even more preferably 10 or less.
[0033] The CNT of this embodiment has a BET specific surface area (X) of 100 m 2 / g or more 1200m 2 / g or less. Preferably 150m 2 / g or more, more preferably 200m 2 / g or more. Also preferably, 2 / g or less, more preferably 800m 2 / g or less. The BET specific surface area of CNTs can be calculated by the BET method using nitrogen adsorption measurements.
[0034] There is often a correlation between the specific surface area of CNTs and the average outer diameter of CNTs. The smaller the specific surface area, the larger the average outer diameter of CNTs and the greater the number of CNTs per mass. On the other hand, the larger the specific surface area of CNTs, the smaller the average outer diameter of CNTs and the fewer the number of CNTs per mass. 2 / g or more, the number of CNTs per mass can be secured, and a conductive network can be efficiently formed. 2 / g or less, the CNTs are well dispersed, and a good conductive network can be formed in the electrode film.
[0035] The average outer diameter of the CNTs in this embodiment is preferably 1 nm or more, more preferably 5 nm or more. The average outer diameter of the CNTs is preferably 15 nm or less, more preferably 13 nm or less, and even more preferably 11 nm or less. When the average outer diameter of the CNTs is 15 nm or less, the number of CNTs per mass can be secured, and a good conductive network can be efficiently formed in the electrode film. When the average outer diameter of the CNTs is 1 nm or more, the dispersion of the CNTs is good, and a good conductive network can be formed in the electrode film.
[0036] The outer diameter and average outer diameter of CNTs are calculated as follows. First, the CNTs are observed and photographed using a transmission electron microscope. Next, 300 CNTs are randomly selected from the photograph and the outer diameter of each is measured. Next, the average outer diameter of the CNTs in nm is calculated as the number average of the outer diameters.
[0037] CNTs usually exist as aggregates. This shape may be, for example, a state in which a single CNT is intricately entangled (entangled), or an aggregate of linear CNTs (bundle-like). A bundle-like CNT aggregate is easier to disentangle than an entangled CNT aggregate. Also, a bundle-like CNT aggregate has better dispersibility than an entangled CNT aggregate, and can therefore be suitably used as a CNT.
[0038] The purity of CNT is expressed as a value (mass%) obtained by subtracting the ash content (mass%) from the mass of CNT. The ash content (mass%) of CNT can be measured, for example, in accordance with JIS K 6218-2. The ash content of CNT is a non-flammable component containing metals and the like. The purity of CNT in this embodiment is preferably 80 mass% or more, more preferably 90 mass% or more, even more preferably 95 mass% or more, and particularly preferably 98 mass% or more, relative to 100 mass% of CNT.
[0039] The CNT content is preferably 0.2% by mass or more, more preferably 0.4% by mass or more, and even more preferably 1% by mass or more, based on the CNT dispersion. Also, it is preferably 30% by mass or less, more preferably 20% by mass or less, and even more preferably 10% by mass or less. By keeping it within the above range, the CNT can be well and stably present without causing precipitation or gelation. In addition, it is preferable to appropriately adjust the CNT content so that a CNT dispersion with appropriate fluidity or viscosity is obtained, depending on the specific surface area of the CNT, affinity to the dispersion medium, dispersibility of the dispersant, etc. The CNT dispersion of the present invention uses dispersant (A) and dispersant (C) as dispersants for CNTs having a specific specific surface area, and ensures dispersion stability by appropriately controlling the amounts added. Therefore, even a dispersion containing a high concentration of CNTs can maintain fluidity over time.
[0040] The CNTs of this embodiment may be CNTs that have been subjected to dry pulverization in order to increase dispersibility. Dry pulverization refers to a process of pulverizing CNTs without the use of a liquid substance. The dry pulverization may be media pulverization, pulverization without media, or a combination of two or more dry pulverizations. For example, in media pulverization, a pulverizer containing pulverization media such as beads or steel balls is used to pulverize particles by utilizing the pulverization force or destructive force caused by the collision between the pulverization media. As the dry pulverization device, a known method such as a dry attritor, ball mill, vibration mill, or bead mill can be used, and the pulverization time can be set arbitrarily depending on the device or the pulverization state of the particles.
[0041] <Dispersant> The CNT dispersion composition of the present embodiment contains two dispersants, dispersant (A) and dispersant (C), used to disperse carbon nanotubes. The dispersant (A) is a polymer containing 80% by mass or more of structural units derived from (meth)acrylic acid, and the dispersant (C) is carboxymethylcellulose or a salt thereof. Other dispersants may be used in combination as long as they do not impair the effect, but it is preferable that the total of the dispersant (A) and the dispersant (C) is the main component.
[0042] [Dispersant (A)] The dispersant (A) is a polymer containing 80% by mass or more of structural units derived from (meth)acrylic acid. The dispersant (A) may be a salt, and may be an organic salt or a metal salt. For example, in the case of an organic salt, ammonium salt, primary ammonium salt, secondary ammonium salt, tertiary ammonium salt, trimethyl-2-hydroxyethylammonium salt, tetramethylammonium salt, cetyltrimethylammonium salt, hexadecyltrimethylammonium salt, trimethylphenylammonium salt, 3-trifluoromethyl-phenyltrimethylammonium salt, benzyltrimethylammonium salt, and other quaternary ammonium salts are listed. In the case of a metal salt, lithium salt, sodium salt, and potassium salt are listed.
[0043] The polymer containing 80% by mass or more of structural units derived from (meth)acrylic acid is a water-soluble resin, and those that are commonly used in adhesives, paints, resin processing of fibers and paper, electrode binders, etc. can be used.
[0044] The structural unit derived from (meth)acrylic acid accounts for 80% by mass or more, based on the mass of the polymer, and preferably 90% by mass or more, although the content may be 100% by mass. When the content is 80 mass% or more, the amount of carboxyl groups adsorbed to the CNTs is sufficient, and when appropriately blended with dispersant (C), they interact with each other and the stability of the dispersion can be maintained over time. In this specification, the content of each structural unit can be determined based on the mass % of the precursor (monomer) that provides each structural unit to the dispersant (A) or the like.
[0045] As the precursor other than (meth)acrylic acid constituting the dispersant (A), various monomers can be appropriately selected and used. Examples of the monomer include a monomer having a carboxyl group other than (meth)acrylic acid, a monomer having a nitrile group, a monomer having a hydroxyl group, and a monomer having a heterocycle.
[0046] From the viewpoint of superior fluidity over time, poly(meth)acrylic acid is preferred, and polyacrylic acid is more preferred.
[0047] The weight average molecular weight of the dispersant (A) of this embodiment is preferably 1,000 or more, more preferably 5,000 or more, and even more preferably 10,000 or more. Also, it is preferably 200,000 or less, more preferably 100,000 or less, and even more preferably 60,000 or less. Also, it is preferable that the pH when dissolved in water is weakly acidic. If it is 1000 or more, it is possible to ensure excellent dispersibility, suppress sedimentation, and ensure stability, while if it is 200,000 or less, it is possible to suppress gelation, which is preferable.
[0048] The content of the dispersant (A) in the CNT dispersion is not particularly limited as long as it satisfies the conditions of (Formula 2) to (Formula 4), and may be appropriately adjusted depending on the specific surface area of the CNTs used and the content of the CNTs in the CNT dispersion, but may be 2% by mass or less, or 0.1% by mass or more. If the content of the dispersant (A) in the CNT dispersion is within the above range, it is preferable because it is possible to eliminate excess carboxyl groups and ensure sufficient dispersing ability.
[0049] [Dispersant (C)] The dispersing agent (C) is carboxymethylcellulose (CMC) or a salt thereof. Carboxymethylcellulose (CMC) or a salt thereof is an anionic water-soluble polymer obtained using cellulose as a raw material.
[0050] The weight average molecular weight of the dispersant (C) is preferably 5,000 or more, more preferably 8,000 or more, and is preferably 100,000 or less, more preferably 70,000 or less, even more preferably 60,000 or less, particularly preferably 30,000 or less, and most preferably 10,000 or less. By setting the weight average molecular weight within the above range, the intermolecular force between the dispersant (C) and the CNTs, and the intermolecular force between the dispersant (C) and water are well balanced, making it possible to disperse the CNTs well and maintain the dispersed state.
[0051] The degree of etherification of the dispersant (C) is preferably 0.5 or more, more preferably 0.6 or more, and is preferably 0.9 or less, more preferably 0.8 or less. By setting the degree of etherification within the above range, it is possible to provide an appropriate affinity for water and CNTs. Furthermore, when used in a secondary battery, it is possible to prevent problems such as the dissolution of the dispersant in the electrolyte in the secondary battery, which increases the viscosity of the electrolyte.
[0052] The method for producing the dispersant (C) is not particularly limited, and it can be produced by a general method for producing CMC or a salt thereof. That is, it is produced by carrying out a mercerization reaction in which an alkali is reacted with cellulose, and then adding an etherification agent to the obtained alkali cellulose to carry out an etherification reaction. For example, it can be produced by carrying out a mercerization reaction using a mixed solvent containing water and an organic solvent, then adding monochloroacetic acid to carry out an etherification reaction, neutralizing the excess alkali with an acid, removing the mixed solvent, washing and drying, and pulverizing. The molecular weight of the cellulose raw material can be reduced by extending the reaction time of the mercerization reaction.
[0053] Since many commercially available CMC or its salts have a molecular weight higher than the above-mentioned preferred range, it may be used after being hydrolyzed in an acidic aqueous solution to reduce the molecular weight. The weight-average molecular weight of the CMC or its salt to be hydrolyzed is preferably greater than 60,000 and less than 500,000. If the weight-average molecular weight exceeds 500,000, the hydrolysis reaction takes time and a large amount of oxidative decomposition products of CMC or its salt are generated, which may make purification difficult. The hydrolysis reaction in an acidic aqueous solution proceeds in a short time when heated and pressurized. The molecular weight of CMC or its salt can be controlled by adjusting the reaction time, temperature, and pH. The reaction can also be stopped by cooling and neutralizing with an alkali to pH 7 or higher. The acid and base can be generally easily obtained.
[0054] The content of the dispersant (C) in the CNT dispersion is not particularly limited as long as it satisfies the conditions of (Formula 2) to (Formula 4), and may be appropriately adjusted depending on the specific surface area of the CNT used and the content of CNT in the CNT dispersion, but may be 2 mass% or less and 0.004 mass% or more. If the content of the dispersant (C) is within the above range, it is preferable because it is efficiently dispersed and gelation can be further suppressed.
[0055] <Dispersion medium> The CNT dispersion of the present invention contains water as a dispersion medium. The dispersion medium is preferably mainly composed of water, but may contain a water-soluble solvent as desired. Examples of the water-soluble solvent include alcohols such as ethanol, propanol, butanol, and propylene glycol monomethyl ether, and N-methyl-2-pyrrolidone (NMP).
[0056] <Optional ingredients> The CNT dispersion of the present invention can contain other additives, such as conductive materials other than CNTs, dispersants other than dispersant (A) and dispersant (C), wetting agents, defoamers, surfactants, pH adjusters, wetting and penetrating agents, antioxidants, preservatives, anti-mold agents, and leveling agents, as necessary, within a range that does not impair the object of the present invention. These additives can be added at any timing, such as before preparation of the dispersion, during dispersion, or after dispersion.
[0057] <Method for producing CNT dispersion liquid> The CNT dispersion liquid of the present invention is preferably produced by, for example, subjecting CNT, dispersant (A), dispersant (C), and water to a dispersion treatment using a dispersion device to finely disperse them. Note that the dispersion treatment can arbitrarily adjust the addition timing of the materials used and can be a multi-stage treatment of two or more times. The dispersants may be added appropriately either simultaneously or sequentially for dispersant (A) and dispersant (C), and may be added either in the pre-dispersion step of CNT or during the dispersion step. By using dispersant (A) and dispersant (C) in appropriate blending amounts according to the specific surface area of CNT, a CNT dispersion body excellent in initial fluidity and maintaining fluidity over time can be obtained.
[0058] Examples of the dispersion device include a kneader, a two-roll mill, a three-roll mill, a planetary mixer, a ball mill, a horizontal sand mill, a vertical sand mill, an annular bead mill, a paint conditioner, an attritor, a high-shear mixer, a high-pressure homogenizer, an ultrasonic homogenizer, etc. In particular, from the viewpoint of promoting the wetting of CNT and dissociating coarse particles, a high-shear mixer is used in the initial step of dispersion, and then, from the viewpoint of dispersing while maintaining the fiber length of CNT, it is most preferable to use a high-pressure homogenizer. The pressure when using a high-pressure homogenizer is preferably 10 to 240 MPa, more preferably 60 to 150 MPa, and even more preferably 60 to 120 MPa.
[0059] Examples of the dispersion method using a dispersion device include batch-type dispersion, pass-type dispersion, etc., and any method may be used, or two or more methods may be combined. Batch dispersion is a method of dispersing only in the dispersing device body without using piping or the like, and also includes circulation dispersion, which will be described later. It is easy to handle, so it is preferable for small-scale production. Pass dispersion is a dispersion method in which the dispersing device body is equipped with a tank that supplies the liquid to be dispersed through piping and a tank that receives the liquid to be dispersed, and the liquid is passed through the dispersing device body. In addition, circulation dispersion is a method in which the liquid to be dispersed that has passed through the dispersing device body is returned to the tank that supplies the liquid to be dispersed, and dispersion is performed while circulating. In either case, the longer the processing time, the more the dispersion progresses, so it is sufficient to repeat the pass or circulation until the desired dispersion state is reached, and the processing amount can be increased by changing the size of the tank or the processing time. Pass dispersion is preferable in that it is easier to homogenize the dispersion state compared to circulation dispersion. Circulation dispersion is preferable in that the work and manufacturing equipment are simple compared to pass dispersion. In the dispersion process, the disintegration of aggregated particles, the loosening, wetting, stabilization, etc. of CNTs proceed sequentially or simultaneously, and the finished dispersion state differs depending on the way of proceeding, so it is preferable to manage the dispersion state in each dispersion process by using various evaluation methods. For example, it can be managed by the method described in the Examples.
[0060] The CNT dispersion liquid can be used to form an electrode film by further adding an electrode active material and, if necessary, a binder resin to prepare an electrode composition. Furthermore, a film formed using a CNT dispersion liquid can also be used as an underlayer in an electrode in order to improve the adhesion between the electrode film and a current collector or to improve the conductivity of the electrode film.
[0061] ≪CNT resin composition≫ The CNT resin composition according to this embodiment includes the above-mentioned CNT dispersion and a binder resin. The CNT resin composition in this specification does not contain an electrode active material. In addition, according to this embodiment, a method for producing a binder resin composition including the above-mentioned CNT dispersion and a binder resin can be provided.
[0062] <Binder resin> The binder resin is a resin that binds various substances together in the electrode film. As the binder resin, a resin known for use in batteries can be used, which is a resin for addition to the dispersion liquid after CNT dispersion. The binder resin can also be used as a thickener.
[0063] As the binder resin, the same CMC or its salt as the CMC contained as the dispersant (C) in the CNT dispersion liquid, or CMC or its salt having different molecular weights, degrees of etherification, etc. may be used. Also, the same polymer as the polymer containing 80% by mass or more of structural units derived from (meth)acrylic acid as the dispersant (A) contained in the CNT dispersion liquid may be used, or a polymer having different structural units, content rates, etc. may be used. Other binder resins include, for example, polymers or copolymers containing ethylene, propylene, vinyl chloride, vinyl acetate, vinyl alcohol, maleic acid, acrylic acid, acrylic acid esters, methacrylic acid, methacrylic acid esters, acrylonitrile, styrene, vinyl butyral, vinyl acetal, vinyl pyrrolidone, etc. as constituent units; polyurethane resins, polyester resins, phenolic resins, epoxy resins, phenoxy resins, urea resins, melamine resins, alkyd resins, acrylic resins, formaldehyde resins, silicone resins, fluorine resins; cellulose resins; elastomers such as styrene-butadiene rubber and fluororubber; conductive resins such as polyaniline and polyacetylene. Also, modified products, mixtures, and copolymers of these resins may be used. Among these, when used as a binder resin for the positive electrode, a polymer or copolymer having a fluorine atom in the molecule from the perspective of resistance, for example, polyvinylidene fluoride, polyvinyl fluoride, tetrafluoroethylene, etc. are preferable. Also, when used as a binder resin for the negative electrode, CMC or its salt having good adhesion, styrene-butadiene rubber, a polymer containing 80% by mass or more of structural units derived from (meth)acrylic acid, etc. are preferable.
[0064] <Manufacturing method of CNT resin composition> The CNT resin composition is preferably produced by mixing and homogenizing a binder resin after producing a CNT dispersion, or the binder resin may be dissolved in advance. The mixing method can be performed by various conventionally known methods, and the composition can be produced using the dispersion device described in the production method of the CNT dispersion. The binder resin in the CNT resin composition may be one type, or two or more types may be used in combination.
[0065] <<Composition for electrode>> The composition for an electrode according to this embodiment contains the above-mentioned CNT dispersion liquid and an electrode active material, and may contain a binder resin as necessary. A preferred electrode composition includes a CNT dispersion, a binder resin, and an electrode active material. Furthermore, according to the present embodiment, it is possible to provide a method for producing a composition for an electrode containing the above-mentioned CNTs, a dispersant, a dispersion medium, and an electrode active material, and a method for producing a composition for an electrode containing the above-mentioned CNTs, a dispersant, a dispersion medium, an electrode active material, and a binder resin.
[0066] <Electrode active material> Electrode active materials are materials that are the basis of battery reactions. Active materials are divided into positive and negative electrode active materials based on their electromotive force. The positive electrode active material is not particularly limited, but may be a metal compound such as a metal oxide or metal sulfide capable of doping or intercalating lithium ions, or a conductive polymer. Examples of the material include oxides of transition metals such as Fe, Co, Ni, and Mn, composite oxides with lithium, and inorganic compounds such as transition metal sulfides. Specifically, MnO, VO, VO 13 , TiO2, or other transition metal oxide powders; composite oxide powders of lithium and transition metals, such as lithium nickel oxide, lithium cobalt oxide, lithium manganate, and lithium manganate with a spinel structure; and lithium iron phosphate-based materials, which are phosphate compounds with an olivine structure. These positive electrode active materials can be used alone or in combination. The inorganic and organic compounds described above may also be mixed. As the negative electrode active material, there is no particular limitation, but those capable of doping or intercalating lithium ions can be used. For example, alloy systems such as metallic Li, its alloys such as tin alloys, silicon alloys, and lead alloys; Li x Fe2O3, Li x Fe3O4, Li x WO2 (x is a number between 0 < x < 1), metal oxide systems such as lithium titanate, lithium vanadate, and lithium silicate; amorphous carbonaceous materials such as soft carbon and hard carbon, or artificial graphite such as highly graphitized carbon materials, or carbonaceous powders such as natural graphite. These negative electrode active materials can be used alone or in combination of two or more. In particular, using a combination of a highly graphitized carbon material and lithium silicate is preferable from the viewpoints of capacity and lifespan.
[0067] The BET specific surface area of the electrode active material is preferably 0.1 to 10 m 2 / g, more preferably 0.2 to 5 m 2 / g, and even more preferably 0.3 to 3 m 2 / g. The average particle diameter of the electrode active material is preferably 0.05 to 100 μm, and more preferably 0.1 to 50 μm. The average particle diameter of the electrode active material as used herein refers to the average value of the particle diameters measured by an electron microscope for the electrode active material.
[0068] The electrode composition is preferably manufactured by mixing and homogenizing the CNT dispersion liquid and the electrode active material, and the binder resin may be dissolved in the CNT dispersion liquid in advance for use. Also, the electrode active material may be added at any timing in the process of manufacturing the CNT dispersion liquid. The dispersion device used for performing the treatment of dispersing the electrode active material is not particularly limited, and the dispersion devices exemplified in the manufacture of the CNT dispersion liquid can be used.
[0069] The content of the electrode active material contained in the electrode composition is preferably 20% by mass or more, more preferably 40% by mass or more, based on 100% by mass of the electrode composition. The content of the electrode active material contained in the electrode composition is preferably 99% by mass or less, more preferably 97% by mass or less, based on 100% by mass of the electrode composition. The above range is preferable from the viewpoint of coatability or productivity, and from the viewpoint of uniformity of the electrode film. The CNT content in the electrode composition is preferably 0.01% by mass or more, and more preferably 0.05% by mass or more, relative to 100% by mass of the electrode active material. The CNT content in the electrode composition is preferably 10% by mass or less, more preferably 5% by mass or less, and even more preferably 3% by mass or less, relative to 100% by mass of the electrode active material. The content of the binder resin in the electrode composition is preferably 0.3% by mass or more, and more preferably 0.7% by mass or more, relative to 100% by mass of the electrode active material. The content of the binder resin in the electrode composition is preferably 20% by mass or less, more preferably 10% by mass or less, and even more preferably 5% by mass or less, relative to 100% by mass of the electrode active material. The solid content of the electrode composition is preferably 30% by mass or more, more preferably 40% by mass or more, based on 100% by mass of the electrode composition, and is preferably 90% by mass or less, more preferably 85% by mass or less, based on 100% by mass of the electrode composition.
[0070] ≪Electrode film≫ The electrode film is obtained by forming an electrode composition into a film, and contains at least carbon nanotubes, a dispersant (A), a dispersant (C), a binder resin, and an electrode active material. The electrode film can be obtained, for example, by preparing a composition for an electrode by adding an electrode active material or the like to the above-mentioned CNT resin composition, and applying or coating the composition for an electrode, etc. Alternatively, for example, the electrode film can be formed by applying the composition for an electrode onto a current collector and removing the volatile content.
[0071] For example, the electrode film is a coating film formed by coating the above-mentioned electrode composition on a collector and drying it. The material and shape of the collector used for the electrode film are not particularly limited, and can be appropriately selected from those suitable for various secondary batteries. For example, the material of the collector can be metals and alloys such as aluminum, copper, nickel, titanium, or stainless steel.
[0072] The method for applying the electrode composition onto the current collector is not particularly limited, and any known method can be used.
[0073] After coating and drying, the coating may be subjected to a rolling treatment using a flat plate press or a calendar roll, etc. The thickness of the electrode film is generally 1 μm or more and 500 μm or less, and preferably 10 μm or more and 300 μm or less.
[0074] ≪Secondary battery≫ The secondary battery according to this embodiment has the above-mentioned electrode film. The electrode film can be used as an electrode of the secondary battery, and is preferably used as an electrode of a non-aqueous electrolyte secondary battery using an organic electrolyte. The non-aqueous electrolyte secondary battery is a battery including a positive electrode, a negative electrode, and an electrolyte containing an organic electrolyte. The electrode film can be used for either the positive electrode or the negative electrode, or for both. In one embodiment, for example, an electrode film obtained by coating a current collector with a composition for an electrode containing a positive electrode active material and drying the same can be used as a positive electrode. In one embodiment, for example, an electrode film obtained by coating a current collector with a composition for an electrode containing a negative electrode active material and drying the same can be used as a negative electrode.
[0075] As the electrolyte, various conventionally known electrolytes capable of moving ions can be used. For example, those containing lithium salts such as LiBF4, LiClO4, LiPF6, LiAsF6, LiSbF6, LiCF3SO3, Li(CF3SO2)2N, LiC4F9SO3, Li(CF3SO2)3C, LiI, LiBr, LiCl, LiAlCl, LiHF2, LiSCN, or LiBPh4 (wherein Ph is a phenyl group) can be used, but are not limited thereto, and those containing sodium salts can also be used. The electrolyte is preferably dissolved in a non-aqueous solvent and used as an electrolytic solution. An all-solid electrolyte or a polymer electrolyte may be used.
[0076] The non-aqueous solvent is not particularly limited, but various solvents suitable for secondary batteries can be used, for example, carbonates such as ethylene carbonate, propylene carbonate, butylene carbonate, dimethyl carbonate, ethyl methyl carbonate, and diethyl carbonate, lactones, glymes, esters, sulfoxides, and nitriles, etc. These solvents may be used alone or in combination of two or more.
[0077] The secondary battery preferably includes a separator, for example, polyethylene nonwoven fabric, polypropylene nonwoven fabric, polyamide nonwoven fabric, and those which have been subjected to a hydrophilic treatment, but are not particularly limited to these.
[0078] The structure of the secondary battery is not particularly limited, but it is usually composed of a positive electrode and a negative electrode, and a separator that is provided as necessary, and can be in various shapes such as a paper type, a cylindrical type, a button type, a laminated type, etc. depending on the purpose of use. EXAMPLES
[0079] The present invention will be described in more detail below with reference to examples. The present invention is not limited to the following examples as long as it does not deviate from the gist of the present invention. In addition, unless otherwise specified, "%" represents "% by mass".
[0080] <Specific surface area of CNT> Using an electronic balance (manufactured by Sartorius, MSA225S100DI), 0.03 g of CNT was weighed, and then dried while degassing at 110 °C for 15 minutes. After that, using a fully automatic specific surface area measuring device (manufactured by MOUNTECH, HM-model1208), the specific surface area of CNT [m 2 / g] was measured.
[0081] <pH measurement of CNT dispersion> The pH of the CNT dispersion was measured at 25 °C using a desktop pH meter (manufactured by METTLER TOLEDO, SevenCompact S220Expert Pro).
[0082] <Evaluation of viscosity of CNT dispersion> The viscosity of the CNT dispersion was measured using a B-type viscometer (manufactured by Toki Sangyo, "BL") at a rotor rotation speed of 6 rpm with the temperature of the dispersion at 25 °C. The lower the viscosity, the better the dispersibility, and the higher the viscosity, the worse the dispersibility. Also, if the obtained dispersion was clearly separated or sedimented, the dispersibility was considered extremely poor. The viscosity of the CNT dispersion is excellent when it is less than 500 mPa·s, good when it is 500 mPa·s or more and less than 2,000 mPa·s, poor when it is 2,000 mPa·s or more and less than 10,000 mPa·s, and extremely poor when it is 10,000 mPa·s or more and there is sedimentation or separation.
[0083] <Evaluation of temporal stability of CNT dispersion> The evaluation of the temporal stability of the CNT dispersion was carried out by measuring the viscosity of the dispersion after 7 days at 40 °C using a B-type viscometer (manufactured by Toki Sangyo, "BL") at a rotor rotation speed of 6 rpm with the temperature of the dispersion at 25 °C. If the viscosity of the CNT dispersion after 7 days at 40 °C is 20,000 mPa·s or less, it can be said that it has a good viscosity from the perspective of operability. Judgment criteria 〇: 20,000 mPa·s or less (good) △: Exceeding 20,000 mPa·s but having fluidity (bad) ×: Over 20,000 mPa s and no fluidity (extremely poor)
[0084] Details of the materials used in the present examples and comparative examples are as follows. <cnt> · 6A: Multi - layer CNT (manufactured by JEIO, JENOTUBE6A, specific surface area 650 m 2 / g) · 10B: Multi - layer CNT (manufactured by JEIO, JENOTUBE10B, specific surface area 235 m 2 / g) · TUBALL: Single - layer CNT (manufactured by OCSiAl, single - wall carbon nanotube, specific surface area 975 m 2 / g) <Dispersant (C)> · APP - 84: Sodium carboxymethyl cellulose (manufactured by Nippon Paper, Sunrose AAPP - 84, average molecular weight 18,000, degree of etherification 0.71) · 7ULC: Sodium carboxymethyl cellulose (manufactured by ASHLAND, BLANOSE CMC 7ULC, degree of etherification 0.65 - 0.90) <Dispersant (A)> · PAA: Polyacrylic acid (manufactured by Fujifilm Wako Pure Chemical Industries, polyacrylic acid 25,000, weight - average molecular weight 25,000) · PMA: Polymethacrylic acid (manufactured by Fujifilm Wako Pure Chemical Industries, weight - average molecular weight 100,000) · AC - 10LP: Polyacrylic acid (manufactured by Toagosei, Julimer AC - 10LP, weight - average molecular weight 50,000)
[0085] <Manufacture of CNT> (Carbon nanotube (CNT - 1)) Charge 10 parts of 10B (CNT) and 200 parts of zirconia beads with a diameter of 2 mm as grinding media, and dry - grind for 15 minutes using a paint conditioner (manufactured by Red Devil) to obtain dry - ground CNT (CNT - 1). The specific surface area was 250 m 2 / g.
[0086] <Manufacture of dispersant> (Dispersant (A - 1)) A reaction vessel equipped with a stirrer, a reflux condenser, a dropping funnel, a thermometer, and a nitrogen inlet tube was prepared. 80 parts of acrylic acid and 20 parts of methyl methacrylate were mixed to prepare a monomer mixture. 20 parts of MEK, 0.3 part of 2-mercaptoethanol (chain transfer agent), and 10% of the monomer mixture were placed in the reaction vessel, mixed, and thoroughly purged with nitrogen gas. On the other hand, the dropping funnel was charged with the remaining 90% of the monomer mixture, 0.27 part of the chain transfer agent, 60 parts of MEK, and 2.2 parts of 2,2'-azobis(2,4-dimethylvaleronitrile) (manufactured by Fujifilm Wako Pure Chemical Corporation, trade name: V-65). While stirring the monomer mixture in the reaction vessel under a nitrogen atmosphere, the temperature was raised to 65°C, and the mixture in the dropping funnel was added dropwise over 3 hours. After 2 hours at 65°C elapsed from the end of the dropwise addition, a solution prepared by dissolving 0.3 part of the polymerization initiator in 5 parts of MEK was added, and the mixture was further aged at 65°C for 2 hours and at 70°C for 2 hours. The solvent of the obtained product was concentrated under reduced pressure to be completely removed, and a resin dispersant (A-1) (weight average molecular weight (Mw): 10,000, acid value 623 mgKOH / g) was prepared.
[0087] <Preparation of CNT Dispersion> (Example 1-1) Into a glass bottle (manufactured by Kashiwa Glass, M-140), 5.0 parts of (CNT-1) as CNT, 0.25 part of 7ULC (CMC), 0.75 part of AC-10LP, 94 parts of ion-exchanged water, and 120 parts of zirconia beads (bead diameter Φ1.25 mm) were charged, and after performing a dispersion treatment for 8 hours using a paint conditioner (manufactured by Red Devil), the zirconia beads were separated to obtain a CNT dispersion (CNT dispersion 1). CNT dispersion 1 contains 5.0 mass% of (CNT-1) as carbon nanotube (A), 0.25 mass% of 7ULC (CMC) as dispersant (C), 0.75 mass% of AC-10LP as dispersant (A), and 94 mass% of water.
[0088] (Examples 1-2 to 1-21) (Comparative Examples 1-1 to 1-10) Except for changing the composition ratios of the materials and mass % shown in Table 1, the same procedure as in Example 1-1 was carried out to obtain CNT dispersions (CNT dispersions 2 to 21, 28 to 37).
[0089] (Examples 1-22) 94 parts of ion-exchanged water was added to a stainless steel container, and while stirring with a disperser, 0.5 parts of 7ULC (CMC) and 0.5 parts of AC-10LP were added and dissolved. Then, 2.0 parts of 10B (CNT) were added while stirring with a disperser, and a square-hole high-shear screen was attached to a high-shear mixer (manufactured by Silverson, L5M-A), and batch dispersion was performed at a speed of 8,600 rpm until the entire mixture became uniform and the dispersion particle size was 250 μm or less using a grind gauge. At this time, the dispersion particle size confirmed by the grind gauge was 180 μm. Next, the liquid to be dispersed was supplied from the stainless steel container to a high-pressure homogenizer (manufactured by Sugino Machine, Starburst HJP-17007) through a pipe, and a circulation-type dispersion process was performed. The dispersion process was performed using a single nozzle chamber with a nozzle diameter of 0.25 mm and a pressure of 100 MPa. After dispersing until the viscosity of the dispersion liquid measured at 60 rpm with a B-type viscometer (TOKI SANGYO, VISCOMETER, MODEL: BL) was 3,000 mPa·s or less, 0.5 parts of 10B (CNT) were further added to the stainless steel container while stirring with a disperser, and a circulation dispersion process was again performed with a high-pressure homogenizer. After dispersing by circulation until the viscosity was 3,000 mPa·s or less with a high-pressure homogenizer, the process of adding 10B to the stainless steel container while stirring with a disperser was repeated a total of six times (total amount of 10B added was 5.0 parts). Subsequently, a dispersion process was performed by a pass type 40 times with the high-pressure homogenizer, and a CNT dispersion liquid (CNT dispersion liquid 22) was obtained. The CNT dispersion 22 contains 5.0 mass % of 10B as the carbon nanotubes (A), 0.50 mass % of 7ULC (CMC) as the dispersant (C), 0.50 mass % of AC-10LP as the dispersant (A), and 94 mass % of water.
[0090] (Examples 1-23) 98.08 parts by mass of ion-exchanged water was added to a stainless steel container, and while stirring with a disperser, 0.24 parts of 7ULC (CMC) and 0.48 parts of AC-10LP were added and dissolved. Then, 1.2 parts of 6A (CNT) were taken and added while stirring with a disperser, and a square-hole high shear screen was attached to a high shear mixer (manufactured by Silverson, L5M-A), and batch dispersion was performed at a speed of 8,600 rpm until the entire mixture became uniform and the dispersion particle size was 250 μm or less using a grind gauge. At this time, the dispersion particle size confirmed by the grind gauge was 180 μm. Next, the liquid to be dispersed was supplied from the stainless steel container to a high-pressure homogenizer (manufactured by Sugino Machine, Starburst HJP-17007) through a pipe, and a circulation type dispersion process was performed. The dispersion process was performed using a single nozzle chamber, with a nozzle diameter of 0.25 mm and a pressure of 100 MPa. Dispersion treatment was carried out 40 times using a high-pressure homogenizer, yielding a CNT dispersion (CNT dispersion 23). The CNT dispersion 23 contains 1.2 mass % of 6A as the carbon nanotube (A), 0.24 mass % of 7ULC (CMC) as the dispersant (C), 0.48 mass % of AC-10LP as the dispersant (A), and 98.08 mass % of water.
[0091] (Examples 1-24) 98 parts of ion-exchanged water was added to a stainless steel container, and 0.1 parts of 7ULC (CMC) and 0.9 parts of AC-10LP were added and dissolved while stirring with a disperser. Then, 1.0 parts of TUBALL (CNT) was taken and added while stirring with a disperser. A square-hole high shear screen was attached to a high shear mixer (manufactured by Silverson, L5M-A), and batch dispersion was performed at a speed of 8,600 rpm until the entire mixture became uniform and the dispersion particle size was 250 μm or less using a grind gauge. At this time, the dispersion particle size confirmed by the grind gauge was 180 μm. Next, the liquid to be dispersed was supplied from the stainless steel container to a high-pressure homogenizer (manufactured by Sugino Machine, Starburst HJP-17007) through a pipe, and a circulation type dispersion process was performed. The dispersion process was performed using a single nozzle chamber with a nozzle diameter of 0.20 mm and a pressure of 150 MPa. Dispersion treatment was carried out using a high-pressure homogenizer with 80 passes to obtain a CNT dispersion liquid (CNT dispersion liquid 24) containing 1.0 part by mass of CNTs. The CNT dispersion 24 contains 1.0 mass % of TUBALL as the carbon nanotubes (A), 0.10 mass % of 7ULC (CMC) as the dispersant (C), 0.90 mass % of AC-10LP as the dispersant (A), and 98 mass % of water.
[0092] (Examples 1-25 to 1-27) (Comparative Examples 1-11 to 1-12) Except for changing the composition ratios of the materials and mass % shown in Table 1, the same procedures as in Examples 1-24 were carried out to obtain CNT dispersions (CNT dispersions 25 to 27, 38 to 39).
[0093] [Table 1-1]
[0094] [Table 1-2]
[0095] It was confirmed that the CNT dispersions of the Examples had lower initial viscosity, better fluidity, and lower viscosity over time than the CNT dispersions of the Comparative Examples, and were therefore superior in operability. Therefore, it can be said that this CNT dispersion can provide a CNT dispersion with a long life cycle and superior operability. In particular, it was confirmed that even a carbon nanotube dispersion containing carbon nanotubes at a high concentration had excellent fluidity over time.
[0096] <Preparation of negative electrode composition and negative electrode> (Example 2-1) Capacity 150cm 3 The CNT dispersion (CNT dispersion 1), MAC500LC (CMC), and water were added to the plastic container, and the mixture was stirred at 2,000 rpm for 30 seconds using a rotation-revolution mixer (Thinki Awatori Rentaro, ARE-310) to obtain a CNT resin composition. Then, artificial graphite and silicon were added to the CNT resin composition as negative electrode active materials, and the mixture was stirred at 2,000 rpm for 150 seconds using the rotation-revolution mixer. Then, SBR was added, and the mixture was stirred at 2,000 rpm for 30 seconds using the rotation-revolution mixer to obtain a negative electrode composition. The nonvolatile content of the negative electrode composition was 48 mass%. The nonvolatile content ratio of artificial graphite:silicon:CNT:CMC (MAC500LC):SBR in the nonvolatile content of the negative electrode composition was 87:10:0.5:1:1.5.
[0097] The obtained negative electrode composition was applied to a copper foil having a thickness of 20 μm using an applicator, and the coating was dried in an electric oven at 120°C ± 5°C for 25 minutes to prepare an electrode film. The electrode film was then rolled using a roll press (3t hydraulic roll press, manufactured by Sun Metals) to obtain a negative electrode (negative electrode 1). The weight per unit area of the electrode film was 10 mg / cm. 2 The density of the composite layer after rolling was 1.6 g / cc.
[0098] The above raw materials are as follows: Silicon: Silicon monoxide (manufactured by Osaka Titanium Technologies, SILICON MONOOXIDE SiO 1.3C 5μm, non-volatile content 100%) Artificial graphite: Graphite (Nippon Graphite Industry, CGB-20, 100% non-volatile content) ·MAC500LC: Carboxymethylcellulose sodium salt (Nippon Paper Industries, Sunrose special type MAC500LC) SBR: Styrene butadiene rubber (JSR, TRD2001, non-volatile content 48%)
[0099] (Examples 2-2 to 2-27, Comparative Examples 2-1 to 2-5, 2-7, 2-8, 2-10 to 2-12) Negative electrodes 2 to 32, 34, 35, and 37 to 39 were obtained in the same manner as in Example 2-1, except that the CNT dispersion was changed to each dispersion shown in Table 2 and the composition ratio was changed to that shown in Table 2.
[0100] <Method for evaluating the conductivity of the negative electrode> The surface resistivity [Ω / □] of the composite layer of the obtained negative electrode was measured using Loresta GP (Mitsubishi Analytec, MCP-T610). After the measurement, the thickness of the electrode film was multiplied to obtain the volume resistivity [Ω·cm] of the negative electrode. The thickness of the electrode film was measured at three points in the electrode using a film thickness meter (NIKON, DIGIMICRO MH-15M), and the thickness of the copper foil was subtracted from the average value to obtain the volume resistivity [Ω·cm] of the negative electrode. <Judgment criteria> ◎: Less than 0.3Ω·cm (Excellent) ○: 0.3Ω·cm or more and less than 0.5Ω·cm (good) ×: 0.5Ω·cm or more (defective)
[0101] [Table 2]
[0102] All of the negative electrodes using the CNT dispersion of the present invention had good electrical conductivity.
[0103] <Preparation of Positive Electrode Composition and Positive Electrode> (Example 3-1) Capacity 150cm 3 The CNT dispersion (CNT dispersion 1), MAC500LC, and water were added to the plastic container, and the mixture was stirred at 2,000 rpm for 30 seconds using a rotation / revolution mixer (Thinky's Awatori Rentaro, ARE-310) to obtain a CNT resin composition. LFP was then added to the CNT resin composition as a positive electrode active material, and the mixture was stirred at 2,000 rpm for 150 seconds using a rotation / revolution mixer (Thinky's Awatori Rentaro, ARE-310). PTFE was then added, and the mixture was stirred at 2,000 rpm for 30 seconds using a rotation / revolution mixer (Thinky's Awatori Rentaro, ARE-310) to obtain a positive electrode composition. The non-volatile content of the positive electrode composition was 75% by mass. The non-volatile content ratio of LFP:conductive material:PTFE:MAC500L in the non-volatile content of the positive electrode composition was 97:0.5:1:1.5.
[0104] The positive electrode composition was applied to an aluminum foil having a thickness of 20 μm using an applicator, and then dried in an electric oven at 120°C ± 5°C for 25 minutes to prepare an electrode film. The electrode film was then rolled using a roll press (3t hydraulic roll press, manufactured by Sun Metals) to obtain a positive electrode (positive electrode 1). The weight per unit area of the electrode film was 20 mg / cm. 2 The density of the electrode film after rolling was 2.1 g / cc.
[0105] The above raw materials are as follows: LFP: Lithium iron phosphate (BASF, HED (trademark) LFP-400, 100% non-volatile content) PTFE: Polytetrafluoroethylene (Daikin Polyflon PTFE D-210C, non-volatile content 60%) ·MAC500LC: Carboxymethylcellulose sodium salt (Nippon Paper Industries, Sunrose special type MAC500LC, non-volatile content 100%)
[0106] (Examples 3-2 to 3-27, Comparative Examples 3-1 to 3-5, 3-7, 3-8, 3-10 to 3-12) Except for changing the CNT dispersion liquid to each dispersion liquid shown in Table 3 and changing the composition ratio to that shown in Table 3, positive electrodes 2 to 32, 34, 35, and 37 to 39 were obtained in the same manner as in Example 3-1.
[0107] <Positive electrode conductivity evaluation method> The conductivity of the obtained positive electrode was evaluated in the same manner as for the negative electrode, except that aluminum foil was used instead of the copper foil. <Judgment criteria> ◎: Less than 10Ω·cm (Excellent) ○: 10Ω·cm or more and less than 20Ω·cm (good) ×: 20Ω·cm or more (defective)
[0108] [Table 3]
[0109] <Preparation of standard positive electrode> As a positive electrode active material, 92% by mass of LFP (HED (trademark) LFP-400, manufactured by BASF, 100% non-volatile content), 4% by mass of acetylene (Denka Black (registered trademark) HS-100, manufactured by Denka, 100% non-volatile content), and 1.6% by mass of a thickener (carboxymethylcellulose #1190, manufactured by Daicel FineChem, 100% non-volatile content) were added to a plastic container, and then mixed until uniform using a spatula. Then, 20.5% by mass of water was added, and the mixture was stirred at 2,000 rpm for 30 seconds using a rotation-revolution mixer (Thinky Awatori Rentaro, ARE-310). Then, the mixture in the plastic container was mixed until uniform using a spatula, and 4% by mass of PTFE (manufactured by Daikin Industries, 60% non-volatile content) was added using a rotation-revolution mixer, and the mixture was stirred at 2,000 rpm for 30 seconds. After that, 11.2% by mass of water was added, and the mixture was stirred at 2,000 rpm for 30 seconds using the planetary centrifugal mixer, and finally, stirred at 3,000 rpm for 10 minutes using a high-speed stirrer to obtain a standard positive electrode composition.
[0110] The standard positive electrode composition described above was applied to an aluminum foil with a thickness of 20 μm as a current collector using an applicator, and then dried in an electric oven at 120°C ± 5°C for 25 minutes to obtain a coating weight per unit area of the electrode of 20 mg / cm. 2 Further, a rolling process was performed using a roll press (Thank Metals, 3 ton hydraulic roll press) to adjust the density of the electrode film to 2.1 g / cm. 3 A standard positive electrode was prepared.
[0111] <Preparation of standard negative electrode> Capacity 150cm 3 0.5% by mass of acetylene black (Denka Black (registered trademark) HS-100, manufactured by Denka), 1% by mass of thickener (Daicel Finechem, carboxyl methyl cellulose #1190, non-volatile content 100%), and 98.4% by mass of water were added to the plastic container, and the mixture was stirred at 2,000 rpm for 30 seconds using a planetary centrifugal mixer (Thinky, Awatori Rentaro, ARE-310). Furthermore, 87% by mass of artificial graphite (Nippon Graphite Industry, CGB-20, non-volatile content 100%) and 10% by mass of silicon (Osaka Titanium Technologies, silicon monoxide SILICON MONOOXIDE SiO 1.3C 5μm, non-volatile content 100%) were added as active materials, and the mixture was stirred at 2,000 rpm for 150 seconds using a planetary centrifugal mixer (Thinky, Awatori Rentaro ARE-310). Next, 3.1% by mass of SBR (TRD2001, manufactured by JSR) was added and the mixture was stirred at 2,000 rpm for 30 seconds using a planetary centrifugal mixer (Thinky's Awatori Rentaro ARE-310) to obtain a standard negative electrode composition. The non-volatile content of the standard negative electrode composition was set to 50% by mass.
[0112] The standard negative electrode composition described above was applied to a 20 μm-thick copper foil current collector using an applicator, and then dried in an electric oven at 80°C ± 5°C for 25 minutes to obtain a coating weight per unit area of the electrode of 10 mg / cm. 2 Further, a rolling process was performed using a roll press (Thank Metals, 3 ton hydraulic roll press) to adjust the density of the electrode film to 1.6 g / cm. 3 A standard negative electrode was prepared.
[0113] <Preparation of secondary battery> Using the negative electrode and positive electrode shown in Tables 4 and 5, each was punched out to 50 mm x 45 mm and 45 mm x 40 mm, and the separator (porous polypropylene film) inserted between them was inserted into an aluminum laminate bag and dried in an electric oven at 70 ° C. for 1 hour. Then, in a glove box filled with argon gas, 2 mL of electrolyte (a mixed solvent of ethylene carbonate, dimethyl carbonate, and diethyl carbonate mixed in a volume ratio of 1:1:1 was prepared, and 1 mass% of vinylene carbonate was added as an additive to 100 mass%, and then LiPF6 was dissolved at a concentration of 1M to form a non-aqueous electrolyte) was injected, and the aluminum laminate was sealed to prepare negative electrode evaluation batteries 1 to 32, 34, 35, 37 to 39 and positive electrode evaluation batteries 1 to 32, 34, 35, 37 to 39, respectively.
[0114] <Method for evaluating rate characteristics of secondary batteries> The obtained negative electrode evaluation battery and positive electrode evaluation battery were placed in a thermostatic chamber at 25°C, and charge / discharge measurements were performed using a charge / discharge device (Hokuto Denko, SM-8). After constant current / constant voltage charging (cutoff current 1mA (0.02C)) at a charge current of 10mA (0.2C) and a charge end voltage of 4.3V, constant current discharging was performed at a discharge current of 10mA (0.2C) and a discharge end voltage of 3V. After repeating this operation three times, constant current / constant voltage charging (cutoff current 1mA (0.02C)) was performed at a charge current of 10mA (0.2C) and a charge end voltage of 4.3V, and constant current discharging was performed at discharge currents of 0.2C and 3C until the discharge end voltage reached 3.0V, and the discharge capacity was calculated for each. The rate characteristic can be expressed as the ratio of the 0.2C discharge capacity to the 3C discharge capacity, as shown below (Equation 5). (Formula 5) Rate characteristic [%] = 3C discharge capacity / 3rd 0.2C discharge capacity × 100 <Judgment criteria> ◎: 80% or more (excellent) ○: 60% or more but less than 80% (good) ×: Less than 60% (defective)
[0115] <Method for evaluating cycle characteristics of secondary batteries> The obtained negative electrode evaluation battery and positive electrode evaluation battery were placed in a thermostatic chamber at 25°C, and charge / discharge measurements were performed using a charge / discharge device (Hokuto Denko, SM-8). After constant current / constant voltage charging (cutoff current 2.5mA (0.05C)) was performed with a charge current of 25mA (0.5C) and a charge end voltage of 4.3V, constant current discharging was performed with a discharge current of 25mA (0.5C) and a discharge end voltage of 3V. This operation was repeated 200 times. The cycle characteristics can be expressed as the ratio of the 3rd 0.5C discharge capacity at 25°C to the 200th 0.5C discharge capacity, as shown below (Equation 6). (Formula 6) Cycle characteristic [%] = 200th 0.5C discharge capacity / 3rd 0.5C discharge capacity × 100 <Judgment criteria> ◎: 85% or more (excellent) ○: 80% or more but less than 85% (good) ×: Less than 80% (defective)
[0116] [Table 4]
[0117] [Table 5]
[0118] The secondary batteries using the CNT dispersions of the respective Examples were excellent in rate characteristics and cycle characteristics. Therefore, it was found that the use of the CNT dispersions of the present invention makes it possible to provide nonaqueous electrolyte secondary batteries having excellent cycle characteristics.
[0119] Furthermore, it was confirmed that the CNT dispersion of the present invention has excellent stability over time even when used after long-term storage, is easy to operate when producing an electrode composition, maintains rate characteristics and cycle characteristics when used as an electrode, can form a good conductive network, and maintains excellent electrical characteristics.< / cnt>
Claims
1. A dispersion medium comprising carbon nanotubes, a dispersant (A), a dispersant (C), and water, The dispersant (A) is a polymer containing 80 mass% or more of structural units derived from (meth)acrylic acid, The dispersant (C) is carboxymethyl cellulose or a salt thereof, A carbon nanotube dispersion liquid that satisfies all of the following (Formula 1) to (Formula 4). (Formula 1) 100≦X≦1200 (Formula 2) Y>0.01 (Formula 3) -0.0005X+0.29≦Y≦-0.0032X+4.32 (Formula 4) 0.05X≦Z≦0.16X ((Formula 1) to (Formula 4), X is the specific surface area of the carbon nanotube [m 2 / g], Y is the ratio of the content of dispersant (C) to the content of dispersant (A) [(C) / (A)], Z is the total content of dispersant (A) and dispersant (C) relative to 100 parts by mass of carbon nanotubes.
2. The carbon nanotube dispersion according to claim 1 , wherein the dispersant (A) is poly(meth)acrylic acid.
3. 2. The carbon nanotube dispersion according to claim 1, wherein the total content of the carbon nanotubes, the dispersant (A), and the dispersant (C) is 90 mass % or more based on the amount of non-volatile components in the carbon nanotube dispersion.
4. 2. The carbon nanotube dispersion according to claim 1, wherein the viscosity of the carbon nanotube dispersion after 7 days at 40° C. is measured using a Brookfield viscometer at 25° C. and a rotation speed of 6 rpm, and is 20,000 mPa·s or less.
5. The carbon nanotube dispersion according to claim 1 , having a pH of 3.0 or more and 7.0 or less.
6. A carbon nanotube resin composition comprising the carbon nanotube dispersion liquid according to any one of claims 1 to 5 and a binder resin.
7. A composition for an electrode, comprising the carbon nanotube resin composition according to claim 6 and an electrode active material.
8. An electrode film formed from the electrode composition according to claim 7.
9. A secondary battery including a positive electrode and a negative electrode, A secondary battery, wherein at least one of a positive electrode and a negative electrode has the electrode film according to claim 8.
Citation Information
Patent Citations
Carbon nanotube water-based dispersion
JP2019212496A
Carbon nanotube dispersion, composition for secondary battery electrodes using the same, electrode membrane, secondary battery
JP2021176140A